Genome-wide association studies of MRI-defined brain infarcts: meta-analysis from the CHARGE Consortium. - Debette, Stephanie; Bis, Joshua C; Fornage, Myriam; Schmidt, Helena; Ikram, M Arfan; Sigurdsson, Sigurdur; Heiss, Gerardo; Struchalin, Maksim; Smith, Albert V; van der Lugt, Aad; DeCarli, Charles; Lumley, Thomas; et al. (Stroke, 2010)
BACKGROUND AND PURPOSE: Previous studies examining genetic associations with MRI-defined brain infarct have yielded inconsistent findings. We investigated genetic variation underlying covert MRI infarct in persons without histories of transient ischemic attack or stroke. We performed meta-analysis of genome-wide association studies of white participants in 6 studies comprising the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Using 2.2 million genotyped and imputed single nucleotide polymorphisms, each study performed cross-sectional genome-wide association analysis of MRI infarct using age- and sex-adjusted logistic regression models. Study-specific findings were combined in an inverse-variance-weighted meta-analysis, including 9401 participants with mean age 69.7 (19.4% of whom had >or=1 MRI infarct). RESULTS: The most significant association was found with rs2208454 (minor allele frequency, 20%), located in intron 3 of MACRO domain containing 2 gene and in the downstream region of fibronectin leucine-rich transmembrane protein 3 gene. Each copy of the minor allele was associated with lower risk of MRI infarcts (odds ratio, 0.76; 95% confidence interval, 0.68-0.84; P=4.64x10(-7)). Highly suggestive associations (P<1.0x10(-5)) were also found for 22 other single nucleotide polymorphisms in linkage disequilibrium (r(2)>0.64) with rs2208454. The association with rs2208454 did not replicate in independent samples of 1822 white and 644 black participants, although 4 single nucleotide polymorphisms within 200 kb from rs2208454 were associated with MRI infarcts in the black population sample. CONCLUSIONS: This first community-based, genome-wide association study on covert MRI infarcts uncovered novel associations. Although replication of the association with top single nucleotide polymorphisms failed, possibly because of insufficient power, results in the black population sample are encouraging, and further efforts at replication are needed.
Keywords: African Americans; Aged; Brain; Brain Infarction; Cohort Studies; DNA Mutational Analysis; Female; Gene Frequency; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

Atrial fibrillation and cognitive decline: a longitudinal cohort study. - Thacker, Evan L; McKnight, Barbara; Psaty, Bruce M; Longstreth, W T; Sitlani, Colleen M; Dublin, Sascha; Arnold, Alice M; Fitzpatrick, Annette L; Gottesman, Rebecca F; Heckbert, Susan R (Neurology, 2013)
OBJECTIVE: We sought to determine whether in the absence of clinical stroke, people with atrial fibrillation experience faster cognitive decline than people without atrial fibrillation. METHODS: We conducted a longitudinal analysis in the Cardiovascular Health Study, a community-based study of 5,888 men and women aged 65 years and older, enrolled in 1989/1990 or 1992/1993. Participants did not have atrial fibrillation or a history of stroke at baseline. Participants were censored when they experienced incident clinical stroke. Incident atrial fibrillation was identified by hospital discharge diagnosis codes and annual study ECGs. The main outcome was rate of decline in mean scores on the 100-point Modified Mini-Mental State Examination (3MSE), administered annually up to 9 times. RESULTS: Analyses included 5,150 participants, of whom 552 (10.7%) developed incident atrial fibrillation during a mean of 7 years of follow-up. Mean 3MSE scores declined faster after incident atrial fibrillation compared with no prior atrial fibrillation. For example, the predicted 5-year decline in mean 3MSE score from age 80 to age 85 was -6.4 points (95% confidence interval [CI]: -7.0, -5.9) for participants without a history of atrial fibrillation, but was -10.3 points (95% CI: -11.8, -8.9) for participants experiencing incident atrial fibrillation at age 80, a 5-year difference of -3.9 points (95% CI: -5.3, -2.5). CONCLUSIONS: In the absence of clinical stroke, people with incident atrial fibrillation are likely to reach thresholds of cognitive impairment or dementia at earlier ages than people with no history of atrial fibrillation.
Keywords: Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cognition Disorders; Comorbidity; Female; Humans; Incidence; Longitudinal Studies; Luria-Nebraska Neuropsychological Battery; Male; Predictive Value of Tests

Blood pressure variability and the risk of all-cause mortality, incident myocardial infarction, and incident stroke in the cardiovascular health study. - Suchy-Dicey, Astrid M; Wallace, Erin R; Mitchell, S V Elkind; Aguilar, Maria; Gottesman, Rebecca F; Rice, Kenneth; Kronmal, Richard; Psaty, Bruce M; Longstreth, W T (Am J Hypertens, 2013)
BACKGROUND: Recent reports have linked variability in visit-to-visit systolic blood pressure (SBP) to risk of mortality and stroke, independent of the effect of mean SBP level. This study aimed to evaluate whether variability in SBP is associated with all-cause mortality, incident myocardial infarction (MI), and incident stroke, independent of mean SBP or trends in SBP levels over time. METHODS: The Cardiovascular Health Study is a longitudinal cohort study of vascular risk factors and disease in the elderly. Participants who attended their first 5 annual clinic visits and experienced no event before the 5th visit were eligible (n = 3,852). Primary analyses were restricted to participants not using antihypertensive medications throughout the first 5 clinic visits (n = 1,642). Intraindividual SBP variables were defined using each participant's 5-visit blood pressure measures. Cox proportional hazards models estimated adjusted hazard ratios (HRs) per SD increase in intraindividual SBP variability, adjusted for intraindividual SBP mean and change over time. RESULTS: Over a mean follow-up of 9.9 years, there were 844 deaths, 203 MIs, and 195 strokes. Intraindividual SBP variability was significantly associated with increased risk of mortality (HR = 1.13; 95% confidence interval (CI) = 1.05-1.21) and of incident MI (HR = 1.20; 95%CI = 1.06-1.36), independent of the effect from adjustment factors. Intraindividual SBP variability was not associated with risk of stroke (HR = 1.03; 95% CI = 0.89-1.21). CONCLUSIONS: Long-term visit-to-visit SBP variability was independently associated with a higher risk of subsequent mortality and MI but not stroke. More research is needed to determine the relationship of BP variability with cardiovascular risk and the clinical implications.
Keywords: Aged; Blood Pressure; Cohort Studies; Female; Humans; Incidence; Longitudinal Studies; Male; Mortality; Myocardial Infarction; Risk; Stroke; United States

Association of kidney disease measures with ischemic versus hemorrhagic strokes: pooled analyses of 4 prospective community-based cohorts. - Mahmoodi, Bakhtawar K; Yatsuya, Hiroshi; Matsushita, Kunihiro; Sang, Yinying; Gottesman, Rebecca F; Astor, Brad C; Woodward, Mark; Longstreth, W T; Psaty, Bruce M; Shlipak, Michael G; Folsom, Aaron R; Gansevoort, Ron T; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Although low glomerular filtration rate (GFR) and albuminuria are associated with increased risk of stroke, few studies compared their contribution to risk of ischemic versus hemorrhagic stroke separately. We contrasted the association of these kidney measures with ischemic versus hemorrhagic stroke. METHODS: We pooled individual participant data from 4 community-based cohorts: 3 from the United States and 1 from The Netherlands. GFR was estimated using both creatinine and cystatin C, and albuminuria was quantified by urinary albumin-to-creatinine ratio (ACR). Associations of estimated GFR and ACR were compared for each stroke type (ischemic versus intraparenchymal hemorrhagic) using study-stratified Cox regression. RESULTS: Among 29,595 participants (mean age, 61 [SD 12.5] years; 46% men; 17% black), 1261 developed stroke (12% hemorrhagic) during 280,549 person-years. Low estimated GFR was significantly associated with increased risk of ischemic stroke, but not hemorrhagic stroke, whereas high ACR was associated with both stroke types. Adjusted hazard ratios for ischemic and hemorrhagic stroke at estimated GFR of 45 (versus 95) mL/min per 1.73 m2 were 1.30 (95% confidence interval, 1.01-1.68) and 0.92 (0.47-1.81), respectively. In contrast, the corresponding hazard ratios for ACR of 300 (versus 5) mg/g were 1.62 (1.27-2.07) for ischemic and 2.57 (1.37-4.83) for hemorrhagic stroke, with significantly stronger association with hemorrhagic stroke (P=0.04). For hemorrhagic stroke, the association of elevated ACR was of similar magnitude as that of elevated systolic blood pressure. CONCLUSIONS: Whereas albuminuria showed significant association with both stroke types, the association of decreased estimated GFR was only significant for ischemic stroke. The strong association of albuminuria with both stroke types warrants clinical attention and further investigations.
Keywords: Aged; Albuminuria; Brain Ischemia; Comorbidity; Female; Glomerular Filtration Rate; Humans; Intracranial Hemorrhages; Kidney Diseases; Male; Middle Aged; Netherlands; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Muzny, Donna; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; European Continental Ancestry Group; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Separate prediction of intracerebral hemorrhage and ischemic stroke. - Ferket, Bart S; van Kempen, Bob J H; Wieberdink, Renske G; Steyerberg, Ewout W; Koudstaal, Peter J; Hofman, Albert; Shahar, Eyal; Gottesman, Rebecca F; Rosamond, Wayne; Kizer, Jorge R; Kronmal, Richard A; Psaty, Bruce M; et al. (Neurology, 2014)
OBJECTIVES: To develop and validate 10-year cumulative incidence functions of intracerebral hemorrhage (ICH) and ischemic stroke (IS). METHODS: We used data on 27,493 participants from 3 population-based cohort studies: the Atherosclerosis Risk in Communities Study, median age 54 years, 45% male, median follow-up 20.7 years; the Rotterdam Study, median age 68 years, 38% male, median follow-up 14.3 years; and the Cardiovascular Health Study, median age 71 years, 41% male, median follow-up 12.8 years. Among these participants, 325 ICH events, 2,559 IS events, and 9,909 nonstroke deaths occurred. We developed 10-year cumulative incidence functions for ICH and IS using stratified Cox regression and competing risks analysis. Basic models including only established nonlaboratory risk factors were extended with diastolic blood pressure, total cholesterol/high-density lipoprotein cholesterol ratio, body mass index, waist-to-hip ratio, and glomerular filtration rate. The cumulative incidence functions' performances were cross-validated in each cohort separately by Harrell C-statistic and calibration plots. RESULTS: High total cholesterol/high-density lipoprotein cholesterol ratio decreased the ICH rates but increased IS rates (p for difference across stroke types <0.001). For both the ICH and IS models, C statistics increased more by model extension in the Atherosclerosis Risk in Communities and Cardiovascular Health Study cohorts. Improvements in C statistics were reproduced by cross-validation. Models were well calibrated in all cohorts. Correlations between 10-year ICH and IS risks were moderate in each cohort. CONCLUSIONS: We developed and cross-validated cumulative incidence functions for separate prediction of 10-year ICH and IS risk. These functions can be useful to further specify an individual's stroke risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Body Mass Index; Brain Ischemia; Cholesterol; Female; Humans; Incidence; Intracranial Hemorrhages; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Risk Assessment; Risk Factors; Stroke

Association between left atrial abnormality on ECG and vascular brain injury on MRI in the Cardiovascular Health Study. - Kamel, Hooman; Bartz, Traci M; Longstreth, W T; Okin, Peter M; Thacker, Evan L; Patton, Kristen K; Stein, Phyllis K; Gottesman, Rebecca F; Heckbert, Susan R; Kronmal, Richard A; Elkind, Mitchell S V; Soliman, Elsayed Z (Stroke, 2015)
BACKGROUND AND PURPOSE: Emerging evidence suggests that atrial disease is associated with vascular brain injury in the absence of atrial fibrillation. METHODS: The Cardiovascular Health Study prospectively enrolled community-dwelling adults aged ≥65 years. Among participants who underwent MRI, we examined associations of ECG left atrial abnormality with brain infarcts and leukoaraiosis. P-wave terminal force in lead V1 was the primary measure of left atrial abnormality; P-wave area and duration were secondary predictors. We excluded participants with atrial fibrillation before or on their index ECG. Primary outcomes were incident infarcts and worsening leukoaraiosis from initial to follow-up scan ≈5 years later. Secondary outcomes were prevalent infarcts and degree of leukoaraiosis on initial MRI. Relative risk (RR) and linear regression models were adjusted for vascular risk factors. RESULTS: Among 3129 participants with ≥1 scan, each SD increase in P-wave terminal force in lead V1 was associated with a 0.05-point (95% confidence interval [CI], 0.0003-0.10) higher baseline white matter grade on a 10-point scale. P-wave terminal force in lead V1 was associated with prevalent infarcts of any type (RR per SD, 1.09; 95% CI, 1.04-1.16) and more so with prevalent nonlacunar infarcts (RR per SD, 1.22; 95% CI, 1.08-1.38). Among 1839 participants with 2 scans, P-wave terminal force in lead V1 was associated with worsening leukoaraiosis (RR per SD, 1.09; 95% CI, 1.01-1.18), but not with incident infarcts (RR per SD, 1.06; 95% CI, 0.93-1.20). Sensitivity analyses adjusting for incident atrial fibrillation found similar results. P-wave area and duration were not associated with outcomes. CONCLUSIONS: ECG left atrial abnormality is associated with vascular brain injury in the absence of documented atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Brain; Brain Infarction; Cardiovascular Diseases; Cerebrovascular Trauma; Electrocardiography; Female; Heart Atria; Heart Diseases; Humans; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Regression Analysis; Risk Factors; Treatment Outcome

Association of Alzheimer's disease GWAS loci with MRI markers of brain aging. - Chauhan, Ganesh; Adams, Hieab H H; Bis, Joshua C; Weinstein, Galit; Yu, Lei; Töglhofer, Anna Maria; Smith, Albert Vernon; van der Lee, Sven J; Gottesman, Rebecca F; Thomson, Russell; Wang, Jing; Yang, Qiong; et al. (Neurobiol Aging, 2015)
Whether novel risk variants of Alzheimer's disease (AD) identified through genome-wide association studies also influence magnetic resonance imaging-based intermediate phenotypes of AD in the general population is unclear. We studied association of 24 AD risk loci with intracranial volume, total brain volume, hippocampal volume (HV), white matter hyperintensity burden, and brain infarcts in a meta-analysis of genetic association studies from large population-based samples (N = 8175-11,550). In single-SNP based tests, AD risk allele of APOE (rs2075650) was associated with smaller HV (p = 0.0054) and CD33 (rs3865444) with smaller intracranial volume (p = 0.0058). In gene-based tests, there was associations of HLA-DRB1 with total brain volume (p = 0.0006) and BIN1 with HV (p = 0.00089). A weighted AD genetic risk score was associated with smaller HV (beta ± SE = -0.047 ± 0.013, p = 0.00041), even after excluding the APOE locus (p = 0.029). However, only association of AD genetic risk score with HV, including APOE, was significant after multiple testing correction (including number of independent phenotypes tested). These results suggest that novel AD genetic risk variants may contribute to structural brain aging in nondemented older community persons.
Keywords: Aging; Alleles; Alzheimer Disease; Apolipoproteins E; Brain; Female; Genome-Wide Association Study; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Organ Size; Polymorphism, Single Nucleotide; Risk; Sialic Acid Binding Ig-like Lectin 3

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

White Matter Lesion Progression: Genome-Wide Search for Genetic Influences. - Hofer, Edith; Cavalieri, Margherita; Bis, Joshua C; DeCarli, Charles; Fornage, Myriam; Sigurdsson, Sigurdur; Srikanth, Velandai; Trompet, Stella; Verhaaren, Benjamin F J; Wolf, Christiane; Yang, Qiong; Adams, Hieab H H; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter lesion (WML) progression on magnetic resonance imaging is related to cognitive decline and stroke, but its determinants besides baseline WML burden are largely unknown. Here, we estimated heritability of WML progression, and sought common genetic variants associated with WML progression in elderly participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Heritability of WML progression was calculated in the Framingham Heart Study. The genome-wide association study included 7773 elderly participants from 10 cohorts. To assess the relative contribution of genetic factors to progression of WML, we compared in 7 cohorts risk models including demographics, vascular risk factors plus single-nucleotide polymorphisms that have been shown to be associated cross-sectionally with WML in the current and previous association studies. RESULTS: A total of 1085 subjects showed WML progression. The heritability estimate for WML progression was low at 6.5%, and no single-nucleotide polymorphisms achieved genome-wide significance (P<5×10(-8)). Four loci were suggestive (P<1×10(-5)) of an association with WML progression: 10q24.32 (rs10883817, P=1.46×10(-6)); 12q13.13 (rs4761974, P=8.71×10(-7)); 20p12.1 (rs6135309, P=3.69×10(-6)); and 4p15.31 (rs7664442, P=2.26×10(-6)). Variants that have been previously related to WML explained only 0.8% to 11.7% more of the variance in WML progression than age, vascular risk factors, and baseline WML burden. CONCLUSIONS: Common genetic factors contribute little to the progression of age-related WML in middle-aged and older adults. Future research on determinants of WML progression should focus more on environmental, lifestyle, or host-related biological factors.
Keywords: Adult; Aged; Cohort Studies; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Middle Aged; Prospective Studies; White Matter

Atrial Cardiopathy and the Risk of Ischemic Stroke in the CHS (Cardiovascular Health Study). - Kamel, Hooman; Bartz, Traci M; Elkind, Mitchell S V; Okin, Peter M; Thacker, Evan L; Patton, Kristen K; Stein, Phyllis K; deFilippi, Christopher R; Gottesman, Rebecca F; Heckbert, Susan R; Kronmal, Richard A; Soliman, Elsayed Z; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: Emerging evidence suggests that an underlying atrial cardiopathy may result in thromboembolism before atrial fibrillation (AF) develops. We examined the association between various markers of atrial cardiopathy and the risk of ischemic stroke. METHODS: The CHS (Cardiovascular Health Study) prospectively enrolled community-dwelling adults ≥65 years of age. For this study, we excluded participants diagnosed with stroke or AF before baseline. Exposures were several markers of atrial cardiopathy: baseline P-wave terminal force in ECG lead V, left atrial dimension on echocardiogram, and N terminal pro B type natriuretic peptide (NT-proBNP), as well as incident AF. Incident AF was ascertained from 12-lead electrocardiograms at annual study visits for the first decade after study enrollment and from inpatient and outpatient Medicare data throughout follow-up. The primary outcome was incident ischemic stroke. We used Cox proportional hazards models that included all 4 atrial cardiopathy markers along with adjustment for demographic characteristics and established vascular risk factors. RESULTS: Among 3723 participants who were free of stroke and AF at baseline and who had data on all atrial cardiopathy markers, 585 participants (15.7%) experienced an incident ischemic stroke during a median 12.9 years of follow-up. When all atrial cardiopathy markers were combined in 1 Cox model, we found significant associations with stroke for P-wave terminal force in ECG lead V (hazard ratio per 1000 μV*ms 1.04; 95% confidence interval, 1.001-1.08), log-transformed NT-proBNP (hazard ratio per doubling of NT-proBNP, 1.09; 95% confidence interval, 1.03-1.16), and incident AF (hazard ratio, 2.04; 95% confidence interval, 1.67-2.48) but not left atrial dimension (hazard ratio per cm, 0.96; 95% confidence interval, 0.84-1.10). CONCLUSIONS: In addition to clinically apparent AF, other evidence of abnormal atrial substrate is associated with subsequent ischemic stroke. This finding is consistent with the hypothesis that thromboembolism from the left atrium may occur in the setting of several different manifestations of atrial disease.

Exome Chip Analysis Identifies Low-Frequency and Rare Variants in for White Matter Hyperintensities on Brain Magnetic Resonance Imaging. - Jian, Xueqiu; Satizabal, Claudia L; Smith, Albert V; Wittfeld, Katharina; Bis, Joshua C; Smith, Jennifer A; Hsu, Fang-Chi; Nho, Kwangsik; Hofer, Edith; Hagenaars, Saskia P; Nyquist, Paul A; Mishra, Aniket; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) on brain magnetic resonance imaging are typical signs of cerebral small vessel disease and may indicate various preclinical, age-related neurological disorders, such as stroke. Though WMH are highly heritable, known common variants explain a small proportion of the WMH variance. The contribution of low-frequency/rare coding variants to WMH burden has not been explored. METHODS: In the discovery sample we recruited 20 719 stroke/dementia-free adults from 13 population-based cohort studies within the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, among which 17 790 were of European ancestry and 2929 of African ancestry. We genotyped these participants at ≈250 000 mostly exonic variants with Illumina HumanExome BeadChip arrays. We performed ethnicity-specific linear regression on rank-normalized WMH in each study separately, which were then combined in meta-analyses to test for association with single variants and genes aggregating the effects of putatively functional low-frequency/rare variants. We then sought replication of the top findings in 1192 adults (European ancestry) with whole exome/genome sequencing data from 2 independent studies. RESULTS: At 17q25, we confirmed the association of multiple common variants in , , and (<6×10). We also identified a novel association with 2 low-frequency nonsynonymous variants in (lead, rs34136221; =4.5×10) partially independent of known common signal (=1.4×10). We further identified a locus at 2q33 containing common variants in , , and (lead, rs2351524; =1.9×10). Although our novel findings were not replicated because of limited power and possible differences in study design, meta-analysis of the discovery and replication samples yielded stronger association for the 2 low-frequency variants (=2.8×10). CONCLUSIONS: Both common and low-frequency/rare functional variants influence WMH. Larger replication and experimental follow-up are essential to confirm our findings and uncover the biological causal mechanisms of age-related WMH.

Genome-wide association study of 23,500 individuals identifies 7 loci associated with brain ventricular volume. - Vojinovic, Dina; Adams, Hieab H; Jian, Xueqiu; Yang, Qiong; Smith, Albert Vernon; Bis, Joshua C; Teumer, Alexander; Scholz, Markus; Armstrong, Nicola J; Hofer, Edith; Saba, Yasaman; Luciano, Michelle; et al. (Nat Commun, 2018)
The volume of the lateral ventricles (LV) increases with age and their abnormal enlargement is a key feature of several neurological and psychiatric diseases. Although lateral ventricular volume is heritable, a comprehensive investigation of its genetic determinants is lacking. In this meta-analysis of genome-wide association studies of 23,533 healthy middle-aged to elderly individuals from 26 population-based cohorts, we identify 7 genetic loci associated with LV volume. These loci map to chromosomes 3q28, 7p22.3, 10p12.31, 11q23.1, 12q23.3, 16q24.2, and 22q13.1 and implicate pathways related to tau pathology, S1P signaling, and cytoskeleton organization. We also report a significant genetic overlap between the thalamus and LV volumes (ρ = -0.59, p-value = 3.14 × 10), suggesting that these brain structures may share a common biology. These genetic associations of LV volume provide insights into brain morphology.

Long-Term Cognitive Decline After Newly Diagnosed Heart Failure: Longitudinal Analysis in the CHS (Cardiovascular Health Study). - Hammond, Christa A; Blades, Natalie J; Chaudhry, Sarwat I; Dodson, John A; Longstreth, W T; Heckbert, Susan R; Psaty, Bruce M; Arnold, Alice M; Dublin, Sascha; Sitlani, Colleen M; Gardin, Julius M; Thielke, Stephen M; et al. (Circ Heart Fail, 2018)
BACKGROUND: Heart failure (HF) is associated with cognitive impairment. However, we know little about the time course of cognitive change after HF diagnosis, the importance of comorbid atrial fibrillation, or the role of ejection fraction. We sought to determine the associations of incident HF with rates of cognitive decline and whether these differed by atrial fibrillation status or reduced versus preserved ejection fraction. METHODS AND RESULTS: Participants were 4864 men and women aged ≥65 years without a history of HF and free of clinical stroke in the CHS (Cardiovascular Health Study)-a community-based prospective cohort study in the United States, with cognition assessed annually from 1989/1990 through 1998/1999. We identified 496 participants with incident HF by review of hospital discharge summaries and Medicare claims data, with adjudication according to standard criteria. Global cognitive ability was measured by the Modified Mini-Mental State Examination. In adjusted models, 5-year decline in model-predicted mean Modified Mini-Mental State Examination score was 10.2 points (95% confidence interval, 8.6-11.8) after incident HF diagnosed at 80 years of age, compared with a mean 5-year decline of 5.8 points (95% confidence interval, 5.3-6.2) from 80 to 85 years of age without HF. The association was stronger at older ages than at younger ages, did not vary significantly in the presence versus absence of atrial fibrillation (=0.084), and did not vary significantly by reduced versus preserved ejection fraction (=0.734). CONCLUSIONS: Decline in global cognitive ability tends to be faster after HF diagnosis than without HF. Clinical and public health implications of this finding warrant further attention.

Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes. - Malik, Rainer; Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Rutten-Jacobs, Loes; Giese, Anne-Katrin; van der Laan, Sander W; Gretarsdottir, Solveig; Anderson, Christopher D; Chong, Michael; et al. (Nat Genet, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci (n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Association Between Blood Pressure and Later-Life Cognition Among Black and White Individuals. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Kabeto, Mohammed U; Hingtgen, Stephanie M; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Elkind, Mitchell S V; Manly, Jennifer J; et al. (JAMA Neurol, 2020)
Importance: Black individuals are more likely than white individuals to develop dementia. Whether higher blood pressure (BP) levels in black individuals explain differences between black and white individuals in dementia risk is uncertain. Objective: To determine whether cumulative BP levels explain racial differences in cognitive decline. Design, Setting, and Participants: Individual participant data from 5 cohorts (January 1971 to December 2017) were pooled from the Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represented a 0.1-SD difference in cognition. The median (interquartile range) follow-up was 12.4 (5.9-21.0) years. Analysis began September 2018. Main Outcomes and Measures: The primary outcome was change in global cognition, and secondary outcomes were change in memory and executive function. Exposures: Race (black vs white). Results: Among 34 349 participants, 19 378 individuals who were free of stroke and dementia and had longitudinal BP, cognitive, and covariate data were included in the analysis. The mean (SD) age at first cognitive assessment was 59.8 (10.4) years and ranged from 5 to 95 years. Of 19 378 individuals, 10 724 (55.3%) were female and 15 526 (80.1%) were white. Compared with white individuals, black individuals had significantly faster declines in global cognition (-0.03 points per year faster [95% CI, -0.05 to -0.01]; P = .004) and memory (-0.08 points per year faster [95% CI, -0.11 to -0.06]; P < .001) but significantly slower declines in executive function (0.09 points per year slower [95% CI, 0.08-0.10]; P < .001). Time-dependent cumulative mean systolic BP level was associated with significantly faster declines in global cognition (-0.018 points per year faster per each 10-mm Hg increase [95% CI, -0.023 to -0.014]; P < .001), memory (-0.028 points per year faster per each 10-mm Hg increase [95% CI, -0.035 to -0.021]; P < .001), and executive function (-0.01 points per year faster per each 10-mm Hg increase [95% CI, -0.014 to -0.007]; P < .001). After adjusting for cumulative mean systolic BP, differences between black and white individuals in cognitive slopes were attenuated for global cognition (-0.01 points per year [95% CI, -0.03 to 0.01]; P = .56) and memory (-0.06 points per year [95% CI, -0.08 to -0.03]; P < .001) but not executive function (0.10 points per year [95% CI, 0.09-0.11]; P < .001). Conclusions and Relevance: These results suggest that black individuals' higher cumulative BP levels may contribute to racial differences in later-life cognitive decline.

Association Between Intracerebral Hemorrhage and Subsequent Arterial Ischemic Events in Participants From 4 Population-Based Cohort Studies. - Murthy, Santosh B; Zhang, Cenai; Diaz, Ivan; Levitan, Emily B; Koton, Silvia; Bartz, Traci M; DeRosa, Janet T; Strobino, Kevin; Colantonio, Lisandro D; Iadecola, Costantino; Safford, Monika M; Howard, Virginia J; et al. (JAMA Neurol, 2021)
Importance: Intracerebral hemorrhage and arterial ischemic disease share risk factors, to our knowledge, but the association between the 2 conditions remains unknown. Objective: To evaluate whether intracerebral hemorrhage was associated with an increased risk of incident ischemic stroke and myocardial infarction. Design, Setting, and Participants: An analysis was conducted of pooled longitudinal participant-level data from 4 population-based cohort studies in the United States: the Atherosclerosis Risk in Communities (ARIC) study, the Cardiovascular Health Study (CHS), the Northern Manhattan Study (NOMAS), and the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study. Patients were enrolled from 1987 to 2007, and the last available follow-up was December 31, 2018. Data were analyzed from September 1, 2019, to March 31, 2020. Exposure: Intracerebral hemorrhage, as assessed by an adjudication committee based on predefined clinical and radiologic criteria. Main Outcomes and Measures: The primary outcome was an arterial ischemic event, defined as a composite of ischemic stroke or myocardial infarction, centrally adjudicated within each study. Secondary outcomes were ischemic stroke and myocardial infarction. Participants with prevalent intracerebral hemorrhage, ischemic stroke, or myocardial infarction at their baseline study visit were excluded. Cox proportional hazards regression was used to examine the association between intracerebral hemorrhage and subsequent arterial ischemic events after adjustment for baseline age, sex, race/ethnicity, vascular comorbidities, and antithrombotic medications. Results: Of 55 131 participants, 47 866 (27 639 women [57.7%]; mean [SD] age, 62.2 [10.2] years) were eligible for analysis. During a median follow-up of 12.7 years (interquartile range, 7.7-19.5 years), there were 318 intracerebral hemorrhages and 7648 arterial ischemic events. The incidence of an arterial ischemic event was 3.6 events per 100 person-years (95% CI, 2.7-5.0 events per 100 person-years) after intracerebral hemorrhage vs 1.1 events per 100 person-years (95% CI, 1.1-1.2 events per 100 person-years) among those without intracerebral hemorrhage. In adjusted models, intracerebral hemorrhage was associated with arterial ischemic events (hazard ratio [HR], 2.3; 95% CI, 1.7-3.1), ischemic stroke (HR, 3.1; 95% CI, 2.1-4.5), and myocardial infarction (HR, 1.9; 95% CI, 1.2-2.9). In sensitivity analyses, intracerebral hemorrhage was associated with arterial ischemic events when updating covariates in a time-varying manner (HR, 2.2; 95% CI, 1.6-3.0); when using incidence density matching (odds ratio, 2.3; 95% CI, 1.3-4.2); when including participants with prevalent intracerebral hemorrhage, ischemic stroke, or myocardial infarction (HR, 2.2; 95% CI, 1.6-2.9); and when using death as a competing risk (subdistribution HR, 1.6; 95% CI, 1.1-2.1). Conclusions and Relevance: This study found that intracerebral hemorrhage was associated with an increased risk of ischemic stroke and myocardial infarction. These findings suggest that intracerebral hemorrhage may be a novel risk marker for arterial ischemic events.

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Pre-Statistical Considerations for Harmonization of Cognitive Instruments: Harmonization of ARIC, CARDIA, CHS, FHS, MESA, and NOMAS. - Briceño, Emily M; Gross, Alden L; Giordani, Bruno J; Manly, Jennifer J; Gottesman, Rebecca F; Elkind, Mitchell S V; Sidney, Stephen; Hingtgen, Stephanie; Sacco, Ralph L; Wright, Clinton B; Fitzpatrick, Annette; Fohner, Alison E; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Meta-analyses of individuals' cognitive data are increasing to investigate the biomedical, lifestyle, and sociocultural factors that influence cognitive decline and dementia risk. Pre-statistical harmonization of cognitive instruments is a critical methodological step for accurate cognitive data harmonization, yet specific approaches for this process are unclear. OBJECTIVE: To describe pre-statistical harmonization of cognitive instruments for an individual-level meta-analysis in the blood pressure and cognition (BP COG) study. METHODS: We identified cognitive instruments from six cohorts (the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, Coronary Artery Risk Development in Young Adults study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study) and conducted an extensive review of each item's administration and scoring procedures, and score distributions. RESULTS: We included 153 cognitive instrument items from 34 instruments across the six cohorts. Of these items, 42%were common across ≥2 cohorts. 86%of common items showed differences across cohorts. We found administration, scoring, and coding differences for seemingly equivalent items. These differences corresponded to variability across cohorts in score distributions and ranges. We performed data augmentation to adjust for differences. CONCLUSION: Cross-cohort administration, scoring, and procedural differences for cognitive instruments are frequent and need to be assessed to address potential impact on meta-analyses and cognitive data interpretation. Detecting and accounting for these differences is critical for accurate attributions of cognitive health across cohort studies.

Sex Differences in Cognitive Decline Among US Adults. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Hingtgen, Stephanie; Elkind, Mitchell S V; Manly, Jennifer J; Gottesman, Rebecca F; et al. (JAMA Netw Open, 2021)
Importance: Sex differences in dementia risk are unclear, but some studies have found greater risk for women. Objective: To determine associations between sex and cognitive decline in order to better understand sex differences in dementia risk. Design, Setting, and Participants: This cohort study used pooled analysis of individual participant data from 5 cohort studies for years 1971 to 2017: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Linear mixed-effects models were used to estimate changes in each continuous cognitive outcome over time by sex. Data analysis was completed from March 2019 to October 2020. Exposure: Sex. Main Outcomes and Measures: The primary outcome was change in global cognition. Secondary outcomes were change in memory and executive function. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1-SD difference in cognition. Results: Among 34 349 participants, 26 088 who self-reported Black or White race, were free of stroke and dementia, and had covariate data at or before the first cognitive assessment were included for analysis. Median (interquartile range) follow-up was 7.9 (5.3-20.5) years. There were 11 775 (44.7%) men (median [interquartile range] age, 58 [51-66] years at first cognitive assessment; 2229 [18.9%] Black) and 14 313 women (median [interquartile range] age, 58 [51-67] years at first cognitive assessment; 3636 [25.4%] Black). Women had significantly higher baseline performance than men in global cognition (2.20 points higher; 95% CI, 2.04 to 2.35 points; P < .001), executive function (2.13 points higher; 95% CI, 1.98 to 2.29 points; P < .001), and memory (1.89 points higher; 95% CI, 1.72 to 2.06 points; P < .001). Compared with men, women had significantly faster declines in global cognition (-0.07 points/y faster; 95% CI, -0.08 to -0.05 points/y; P < .001) and executive function (-0.06 points/y faster; 95% CI, -0.07 to -0.05 points/y; P < .001). Men and women had similar declines in memory (-0.004 points/y faster; 95% CI, -0.023 to 0.014; P = .61). Conclusions and Relevance: The results of this cohort study suggest that women may have greater cognitive reserve but faster cognitive decline than men, which could contribute to sex differences in late-life dementia.
Keywords: Aged; Cognitive Dysfunction; Cognitive Reserve; Cohort Studies; Executive Function; Humans; Memory; Middle Aged; Risk; Sex Factors; Time Factors; United States

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2022)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at approximately 450,000 CpG sites in 9,732 middle-aged to older adults from 14 community-based studies. Single-CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single-CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5), and colocalized with FOLH1 expression in brain (posterior probability =0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single-CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis, and multi-omics colocalization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug repositioning analysis indicated antihyperlipidemic agents, more specifically peroxisome proliferator-activated receptor alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood brain barrier disruption.

Association Between Acute Myocardial Infarction and Cognition. - Johansen, Michelle C; Ye, Wen; Gross, Alden; Gottesman, Rebecca F; Han, Dehua; Whitney, Rachael; Briceño, Emily M; Giordani, Bruno J; Shore, Supriya; Elkind, Mitchell S V; Manly, Jennifer J; Sacco, Ralph L; et al. (JAMA Neurol, 2023)
IMPORTANCE: The magnitude of cognitive change after incident myocardial infarction (MI) is unclear. OBJECTIVE: To assess whether incident MI is associated with changes in cognitive function after adjusting for pre-MI cognitive trajectories. DESIGN, SETTING, AND PARTICIPANTS: This cohort study included adults without MI, dementia, or stroke and with complete covariates from the following US population-based cohort studies conducted from 1971 to 2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Data were analyzed from July 2021 to January 2022. EXPOSURES: Incident MI. MAIN OUTCOMES AND MEASURES: The main outcome was change in global cognition. Secondary outcomes were changes in memory and executive function. Outcomes were standardized as mean (SD) T scores of 50 (10); a 1-point difference represented a 0.1-SD difference in cognition. Linear mixed-effects models estimated changes in cognition at the time of MI (change in the intercept) and the rate of cognitive change over the years after MI (change in the slope), controlling for pre-MI cognitive trajectories and participant factors, with interaction terms for race and sex. RESULTS: The study included 30 465 adults (mean [SD] age, 64 [10] years; 56% female), of whom 1033 had 1 or more MI event, and 29 432 did not have an MI event. Median follow-up was 6.4 years (IQR, 4.9-19.7 years). Overall, incident MI was not associated with an acute decrease in global cognition (-0.18 points; 95% CI, -0.52 to 0.17 points), executive function (-0.17 points; 95% CI, -0.53 to 0.18 points), or memory (0.62 points; 95% CI, -0.07 to 1.31 points). However, individuals with incident MI vs those without MI demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21 to -0.10 points per year), memory (-0.13 points per year; 95% CI, -0.22 to -0.04 points per year), and executive function (-0.14 points per year; 95% CI, -0.20 to -0.08 points per year) over the years after MI compared with pre-MI slopes. The interaction analysis suggested that race and sex modified the degree of change in the decline in global cognition after MI (race × post-MI slope interaction term, P = .02; sex × post-MI slope interaction term, P = .04), with a smaller change in the decline over the years after MI in Black individuals than in White individuals (difference in slope change, 0.22 points per year; 95% CI, 0.04-0.40 points per year) and in females than in males (difference in slope change, 0.12 points per year; 95% CI, 0.01-0.23 points per year). CONCLUSIONS: This cohort study using pooled data from 6 cohort studies found that incident MI was not associated with a decrease in global cognition, memory, or executive function at the time of the event compared with no MI but was associated with faster declines in global cognition, memory, and executive function over time. These findings suggest that prevention of MI may be important for long-term brain health.

Association of Obesity With Cognitive Decline in Black and White Americans. - Quaye, Emmanuel; Galecki, Andrzej T; Tilton, Nicholas; Whitney, Rachael; Briceño, Emily M; Elkind, Mitchell S V; Fitzpatrick, Annette L; Gottesman, Rebecca F; Griswold, Michael; Gross, Alden L; Heckbert, Susan R; Hughes, Timothy M; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: There are disparities in the prevalence of obesity by race, and the relationship between obesity and cognitive decline is unclear. The objective of this study was to determine whether obesity is independently associated with cognitive decline and whether the association between obesity and cognitive decline differs in Black and White adults. We hypothesized that obesity is associated with greater cognitive decline compared with normal weight and that the effect of obesity on cognitive decline is more pronounced in Black adults compared with their White counterparts. METHODS: We pooled data from 28,867 participants free of stroke and dementia (mean, SD: age 61 [10.7] years at the first cognitive assessment, 55% female, 24% Black, and 29% obese) from 6 cohorts. The primary outcome was the annual change in global cognition. We performed linear mixed-effects models with and without time-varying cumulative mean systolic blood pressure (SBP) and fasting plasma glucose (FPG). Global cognition was set to a t-score metric (mean 50, SD 10) at a participant's first cognitive assessment; a 1-point difference represents a 0.1 SD difference in global cognition across the 6 cohorts. The median follow-up was 6.5 years (25th percentile, 75th percentile: 5.03, 20.15). RESULTS: Obese participants had lower baseline global cognition than normal-weight participants (difference in intercepts, -0.36 [95% CI, -0.46 to -0.17]; < 0.001). This difference in baseline global cognition was attenuated but was borderline significant after accounting for SBP and FPG (adjusted differences in intercepts, -0.19 [95% CI, -0.39 to 0.002]; = 0.05). There was no difference in the rate of decline in global cognition between obese and normal-weight participants (difference in slope, 0.009 points/year [95% CI, -0.009 to 0.03]; = 0.32). After accounting for SBP and FPG, obese participants had a slower decline in global cognition (adjusted difference in slope, 0.03 points/year slower [95% CI, 0.01 to 0.05]; < 0.001). There was no evidence that race modified the association between body mass index and global cognitive decline ( = 0.34). DISCUSSION: These results suggest that obesity is associated with lower initial cognitive scores and may potentially attenuate declines in cognition after accounting for BP and FPG.
Keywords: Aged; Black or African American; Cognition; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Obesity; Risk Factors; United States; White

Prediction of Multiple Individual Primary Cardiovascular Events Using Pooled Cohorts. - Sussman, Jeremy B; Whitney, Rachael T; Burke, James F; Hayward, Rodney A; Galecki, Andrzej; Sidney, Stephen; Allen, Norrina Bai; Gottesman, Rebecca F; Heckbert, Susan R; Longstreth, William T; Psaty, Bruce M; Elkind, Mitchell S V; et al. (medRxiv, 2023)
INTRODUCTION: Most current clinical risk prediction scores for cardiovascular disease prevention use a composite outcome. Risk prediction scores for specific cardiovascular events could identify people who are at higher risk for some events than others informing personalized care and trial recruitment. We sought to predict risk for multiple different events, describe how those risks differ, and examine if these differences could improve treatment priorities. METHODS: We used participant-level data from five cohort studies. We included participants between 40 and 79 years old who had no history of myocardial infarction (MI), stroke, or heart failure (HF). We made separate models to predict 10-year rates of first atherosclerotic cardiovascular disease (ASCVD), first fatal or nonfatal MI, first fatal or nonfatal stroke, new-onset HF, fatal ASCVD, fatal MI, fatal stroke, and all-cause mortality using established ASCVD risk factors. To limit overfitting, we used elastic net regularization with alpha = 0.75. We assessed the models for calibration, discrimination, and for correlations between predicted risks for different events. We also estimated the potential impact of varying treatment based on patients who are high risk for some ASCVD events, but not others. RESULTS: Our study included 24,505 people; 55.6% were women, and 20.7% were non-Hispanic Black. Our models had C-statistics between 0.75 for MI and 0.85 for HF, good calibration, and minimal overfitting. The models were least similar for fatal stroke and all MI (0.58). In 1,840 participants whose risk of MI but not stroke or all-cause mortality was in the top quartile, we estimate one blood pressure-lowering medication would have a 2.4% chance of preventing any ASCVD event per 10 years. A moderate-strength statin would have a 2.1% chance. In 1,039 participants who had top quartile risk of stroke but not MI or mortality, a blood pressure-lowering medication would have a 2.5% chance of preventing an event, but a moderate-strength statin, 1.6%. CONCLUSION: We developed risk scores for eight key clinical events and found that cardiovascular risk varies somewhat for different clinical events. Future work could determine if tailoring decisions by risk of separate events can improve care.

Sleep Architecture, Obstructive Sleep Apnea, and Cognitive Function in Adults. - Pase, Matthew P; Harrison, Stephanie; Misialek, Jeffrey R; Kline, Christopher E; Cavuoto, Marina; Baril, Andree-Ann; Yiallourou, Stephanie; Bisson, Alycia; Himali, Dibya; Leng, Yue; Yang, Qiong; Seshadri, Sudha; et al. (JAMA Netw Open, 2023)
IMPORTANCE: Good sleep is essential for health, yet associations between sleep and dementia risk remain incompletely understood. The Sleep and Dementia Consortium was established to study associations between polysomnography (PSG)-derived sleep and the risk of dementia and related cognitive and brain magnetic resonance imaging endophenotypes. OBJECTIVE: To investigate association of sleep architecture and obstructive sleep apnea (OSA) with cognitive function in the Sleep and Dementia Consortium. DESIGN, SETTING, AND PARTICIPANTS: The Sleep and Dementia Consortium curated data from 5 population-based cohorts across the US with methodologically consistent, overnight, home-based type II PSG and neuropsychological assessments over 5 years of follow-up: the Atherosclerosis Risk in Communities study, Cardiovascular Health Study, Framingham Heart Study (FHS), Osteoporotic Fractures in Men Study, and Study of Osteoporotic Fractures. Sleep metrics were harmonized centrally and then distributed to participating cohorts for cohort-specific analysis using linear regression; study-level estimates were pooled in random effects meta-analyses. Results were adjusted for demographic variables, the time between PSG and neuropsychological assessment (0-5 years), body mass index, antidepressant use, and sedative use. There were 5946 participants included in the pooled analyses without stroke or dementia. Data were analyzed from March 2020 to June 2023. EXPOSURES: Measures of sleep architecture and OSA derived from in-home PSG. MAIN OUTCOMES AND MEASURES: The main outcomes were global cognitive composite z scores derived from principal component analysis, with cognitive domains investigated as secondary outcomes. Higher scores indicated better performance. RESULTS: Across cohorts, 5946 adults (1875 females [31.5%]; mean age range, 58-89 years) were included. The median (IQR) wake after sleep onset time ranged from 44 (27-73) to 101 (66-147) minutes, and the prevalence of moderate to severe OSA ranged from 16.9% to 28.9%. Across cohorts, higher sleep maintenance efficiency (pooled β per 1% increase, 0.08; 95% CI, 0.03 to 0.14; P < .01) and lower wake after sleep onset (pooled β per 1-min increase, -0.07; 95% CI, -0.13 to -0.01 per 1-min increase; P = .02) were associated with better global cognition. Mild to severe OSA (apnea-hypopnea index [AHI] ≥5) was associated with poorer global cognition (pooled β, -0.06; 95% CI, -0.11 to -0.01; P = .01) vs AHI less than 5; comparable results were found for moderate to severe OSA (pooled β, -0.06; 95% CI, -0.11 to -0.01; P = .02) vs AHI less than 5. Differences in sleep stages were not associated with cognition. CONCLUSIONS AND RELEVANCE: This study found that better sleep consolidation and the absence of OSA were associated with better global cognition over 5 years of follow-up. These findings suggest that the role of interventions to improve sleep for maintaining cognitive function requires investigation.

Cumulative Systolic Blood Pressure and Incident Stroke Type Variation by Race and Ethnicity. - Johnson, Kimson E; Li, Hanyu; Zhang, Min; Springer, Mellanie V; Galecki, Andrzej T; Whitney, Rachael T; Gottesman, Rebecca F; Hayward, Rodney A; Sidney, Stephen; Elkind, Mitchell S V; Longstreth, W T; Heckbert, Susan R; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Stroke risk varies by systolic blood pressure (SBP), race, and ethnicity. The association between cumulative mean SBP and incident stroke type is unclear, and whether this association differs by race and ethnicity remains unknown. OBJECTIVE: To examine the association between cumulative mean SBP and first incident stroke among 3 major stroke types-ischemic stroke (IS), intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH)-and explore how these associations vary by race and ethnicity. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data from 6 US longitudinal cohorts (January 1, 1971, to December 31, 2019) were pooled. The analysis was performed from January 1, 2022, to January 2, 2024. The median follow-up was 21.6 (IQR, 13.6-31.8) years. EXPOSURE: Time-dependent cumulative mean SBP. MAIN OUTCOMES AND MEASURES: The primary outcome was time from baseline visit to first incident stroke. Secondary outcomes consisted of time to first incident IS, ICH, and SAH. RESULTS: Among 40 016 participants, 38 167 who were 18 years or older at baseline with no history of stroke and at least 1 SBP measurement before the first incident stroke were included in the analysis. Of these, 54.0% were women; 25.0% were Black, 8.9% were Hispanic of any race, and 66.2% were White. The mean (SD) age at baseline was 53.4 (17.0) years and the mean (SD) SBP at baseline was 136.9 (20.4) mm Hg. A 10-mm Hg higher cumulative mean SBP was associated with a higher risk of overall stroke (hazard ratio [HR], 1.20 [95% CI, 1.18-1.23]), IS (HR, 1.20 [95% CI, 1.17-1.22]), and ICH (HR, 1.31 [95% CI, 1.25-1.38]) but not SAH (HR, 1.13 [95% CI, 0.99-1.29]; P = .06). Compared with White participants, Black participants had a higher risk of IS (HR, 1.20 [95% CI, 1.09-1.33]) and ICH (HR, 1.67 [95% CI, 1.30-2.13]) and Hispanic participants of any race had a higher risk of SAH (HR, 3.81 [95% CI, 1.29-11.22]). There was no consistent evidence that race and ethnicity modified the association of cumulative mean SBP with first incident stroke and stroke type. CONCLUSIONS AND RELEVANCE: The findings of this cohort study suggest that cumulative mean SBP was associated with incident stroke type, but the associations did not differ by race and ethnicity. Culturally informed stroke prevention programs should address modifiable risk factors such as SBP along with social determinants of health and structural inequities in society.
Keywords: Adult; Aged; Black or African American; Blood Pressure; Cerebral Hemorrhage; Ethnicity; Female; Hispanic or Latino; Humans; Hypertension; Incidence; Ischemic Stroke; Longitudinal Studies; Male; Middle Aged; Racial Groups; Risk Factors; Stroke; Subarachnoid Hemorrhage; United States; White; White People

Plasma proteome-wide analysis of cerebral small vessel disease identifies novel biomarkers and disease pathways. - Gomez, Gabriela T; Shi, Liu; Fohner, Alison E; Chen, Jingsha; Yang, Yunju; Fornage, Myriam; Duggan, Michael R; Peng, Zhongsheng; Daya, Gulzar N; Tin, Adrienne; Schlosser, Pascal; Longstreth, W T; et al. (medRxiv, 2024)
Cerebral small vessel disease (SVD), as defined by neuroimaging characteristics such as white matter hyperintensities (WMHs), cerebral microhemorrhages (CMHs), and lacunar infarcts, is highly prevalent and has been associated with dementia risk and other clinical sequelae. Although conditions such as hypertension are known to contribute to SVD, little is known about the diverse set of subclinical biological processes and molecular mediators that may also influence the development and progression of SVD. To better understand the mechanisms underlying SVD and to identify novel SVD biomarkers, we used a large-scale proteomic platform to relate 4,877 plasma proteins to MRI-defined SVD characteristics within 1,508 participants of the Atherosclerosis Risk in Communities (ARIC) Study cohort. Our proteome-wide analysis of older adults (mean age: 76) identified 13 WMH-associated plasma proteins involved in synaptic function, endothelial integrity, and angiogenesis, two of which remained associated with late-life WMH volume when measured nearly 20 years earlier, during midlife. We replicated the relationship between 9 candidate proteins and WMH volume in one or more external cohorts; we found that 11 of the 13 proteins were associated with risk for future dementia; and we leveraged publicly available proteomic data from brain tissue to demonstrate that a subset of WMH-associated proteins was differentially expressed in the context of cerebral atherosclerosis, pathologically-defined Alzheimer's disease, and cognitive decline. Bidirectional two-sample Mendelian randomization analyses examined the causal relationships between candidate proteins and WMH volume, while pathway and network analyses identified discrete biological processes (lipid/cholesterol metabolism, NF-kB signaling, hemostasis) associated with distinct forms of SVD. Finally, we synthesized these findings to identify two plasma proteins, oligodendrocyte myelin glycoprotein (OMG) and neuronal pentraxin receptor (NPTXR), as top candidate biomarkers for elevated WMH volume and its clinical manifestations.

Sleep macro-architecture and dementia risk in adults: Meta-analysis of 5 cohorts from the Sleep and Dementia Consortium. - Yiallourou, Stephanie; Baril, Andree-Ann; Wiedner, Crystal; Misialek, Jeffrey R; Kline, Christopher E; Harrison, Stephanie; Cannon, Ethan; Yang, Qiong; Bernal, Rebecca; Bisson, Alycia; Himali, Dibya; Cavuoto, Marina; et al. (medRxiv, 2024)
STUDY OBJECTIVES: Poor sleep may play a role in the risk of dementia. However, few studies have investigated the association between polysomnography (PSG)-derived sleep architecture and dementia incidence. We examined the relationship between sleep macro-architecture and dementia incidence across five US-based cohort studies from the Sleep and Dementia Consortium (SDC). METHODS: Percent of time spent in stages of sleep (N1, N2, N3, REM sleep), wake after sleep onset and sleep maintenance efficiency were derived from a single night home-based PSG. Dementia was ascertained in each cohort using its cohort-specific criteria. Each cohort performed Cox proportional hazard regressions for each sleep exposure and incident dementia, adjusting for age, sex, body mass index, anti-depressant use, sedative use, and status. Results were then pooled in random effects meta-analyses. RESULTS: The pooled sample comprised 4,657 participants (30% women) aged ≥60 years (mean age was 74 years at sleep assessment). There were 998 (21.4%) dementia cases (median follow-up time of 5 to 19 years). Pooled effects of the five cohorts showed no association between sleep architecture and incident dementia. When meta-analyses were restricted to the three cohorts which had dementia case ascertainment based on DSM-IV/V criteria (n=2,374), higher N3% was marginally associated with an increased risk of dementia (HR: 1.06; 95%CI: 1.00-1.12, per percent increase N3, p=0.050). CONCLUSIONS: There were no consistent associations between sleep macro-architecture measured and the risk of incident dementia. Implementing more nuanced sleep metrics remains an important next step for uncovering more about sleep-dementia associations.

Trajectory of Cognitive Function After Incident Heart Failure. - Shore, Supriya; Li, Hanyu; Zhang, Min; Whitney, Rachael; Gross, Alden L; Bhatt, Ankeet S; Nallamothu, Brahmajee K; Giordani, Bruno; Briceño, Emily M; Sussman, Jeremy B; Gutierrez, Jose; Yaffe, Kristine; et al. (medRxiv, 2024)
BACKGROUND: The size/magnitude of cognitive changes after incident heart failure (HF) are unclear. We assessed whether incident HF is associated with changes in cognitive function after accounting for pre-HF cognitive trajectories and known determinants of cognition. METHODS: This pooled cohort study included adults without HF, stroke, or dementia from six US population-based cohort studies from 1971-2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Linear mixed-effects models estimated changes in cognition at the time of HF (change in the intercept) and the rate of cognitive change over the years after HF (change in the slope), controlling for pre-HF cognitive trajectories and participant factors. Change in global cognition was the primary outcome. Change in executive function and memory were secondary outcomes. Cognitive outcomes were standardized to a -score metric (mean [SD], 50 [10]); a 1-point difference represented a 0.1-SD difference in cognition. RESULTS: The study included 29,614 adults (mean [SD] age was 61.1 [10.5] years, 55% female, 70.3% White, 22.2% Black 7.5% Hispanic). During a median follow-up of 6.6 (Q1-Q3: 5-19.8) years, 1,407 (4.7%) adults developed incident HF. Incident HF was associated with an acute decrease in global cognition (-1.08 points; 95% CI -1.36, -0.80) and executive function (-0.65 points; 95% CI -0.96, -0.34) but not memory (-0.51 points; 95% CI -1.37, 0.35) at the time of the event. Greater acute decreases in global cognition after HF were seen in those with older age, female sex and White race. Individuals with incident HF, compared to HF-free individuals, demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21, -0.09) and executive function (-0.16 points per year; 95% CI -0.23, -0.09) but not memory ( -0.11 points per year; 95% CI -0.26, 0.04) compared with pre-HF slopes. CONCLUSIONS: In this pooled cohort study, incident HF was associated with an acute decrease in global cognition and executive function at the time of the event and faster declines in global cognition and executive function over the following years.